Assessment of the results of endodontic treatment of teeth - S. N. Razumova; A. S. Brago; Haydar Barakat; L. M. Khaskhanova; R. M. Bragunova (Эндодонтия Today)
The success of endodontic treatment depends on many factors. The most important of them are the knowledge and manual skills of the dentist.Materials and methods. We analyzed the condition of teeth after endodontic treatment in 300 patients aged 20 to 70 years. Were studied 300 images of CBCT, the number of treated teeth and the number of cases of unsuccessful endodontic treatment was analyzed.Results. According to CBCT data, high-quality obturation of the root canal system was observed in 1335 (75%) endodontically treated teeth. The reasons for successful endodontic treatment are under-sealing of the root canal (16%), removal of material beyond the apex (5.6%), and missed root canals (3.4%).Conclusion. Clinical dental patient examination revealed that maxillary and mandibular molars most often undergo endodontic treatment.